Main-group metal cyclophane complexes with high coordination numbers. Issue 51 (20th August 2020) - Altaf, Yasir; Yar, Muhammad; Hashmi, Muhammad Ali
Abstract : Investigation of the complexation of main-group metal-cations with [2.2.2] para cyclophane and deltaphane. Abstract : Density functional theory calculations using the PBE0-D3BJ hybrid functional have been employed to investigate the complexation of main-group metal-cations with [2.2.2] para cyclophane and deltaphane. Geometry optimization under symmetry constraints was performed to observe the mode of coordination that a metal-cation adopts when it resides inside the cyclophane cavity. Thermodynamic properties were investigated to note the trends of stability along a group of metals. To further investigate the bonding properties, Morokuma–Ziegler energy decomposition analysis, natural bond orbital analysis and Bader's analysis were employed. It was observed that most of the main-group metal complexes with cyclophanes prefer an η 6 η 6 η 6 coordination mode where the metal-cation sits in the centre of the cyclophane cavity. There is an increased thermodynamic stability in [2.2.2] para cyclophane complexes compared to their deltaphane analogues while the reverse is true regarding the strength of coordination based on interaction energy.